Дифракция плоской волны на двухслойной фотонно-кристаллической структуре из магнитодиэлектрика - Шматько, А. А.; Казанко, А. В.; Мизерник, В. Н.; Одаренко, Е. Н. (Харківський національний університет радіоелектроніки, 2015)
The problem of diffraction of the E-polarized wave on the finite two-layer periodic photonic crystal structure (magnetodielectric gratings) with various material parameters is considered in this report. The problem is solved in rigorous mathematical definition for any relations between a wave length and the characteristic dimensions of the structure. The special emphasis was given to the numerical solution of the dispersion equation that defines the spectral characteristics of the field in the photonic crystal structure with the finite dimensions. The combined magnetodielectric and metamaterial gratings are considered. The fundamental features of the waves propagation in the phase gratings with layers that have identical refraction indexes have been analyzed.
Keywords: фотонный кристалл; магнитодиэлектрик; дифракционная решетка